Differential Diagnosis of Vertigo in the Emergency Department: A Prospective Validation Study of the STANDING Algorithm - Vanni, Simone; Pecci, Rudi; Edlow, Jonathan A.; Nazerian, Peiman; Santimone, Rossana; Pepe, Giuseppe; Moretti, Marco; Pavellini, Andrea; Caviglioli, Cosimo; Casula, Claudia; Bigiarini, Sofia; Vannucchi, Paolo; et al. (Frontiers in Neurology, 2017)
Objective. We investigated the reliability and accuracy of a bedside diagnostic algorithm for patients presenting with vertigo/unsteadiness to the emergency department. Methods. We enrolled consecutive adult patients presenting with vertigo/unsteadiness at a tertiary hospital. STANDING, the acronym for the four-step algorithm we have previously described, based on nystagmus observation and well known diagnostic manoeuvres, includes 1) the discrimination between SponTAneous and positional nystagmus, 2) the evaluation of the Nystagmus Direction, 3) the head Impulse test and 4) the evaluation of equilibrium (staNdinG). Reliability of each step was analysed by Fleiss’ k calculation. The reference standard (central vertigo) was a composite of brain disease including stroke, demyelinating disease, neoplasm, or other brain disease diagnosed by initial imaging or during 3-month follow-up. Results. Three hundred and fifty-two patients were included. The incidence of central vertigo was 11.4% (95% CI 8.2%-15.2%). The leading cause was ischemic stroke (70%). The STANDING showed a good reliability (overall Fleiss K 0.83), the second step showing the highest (0.95) and the third step the lowest (0.74) agreement. The overall accuracy of the algorithm was good (88%, 95% CI 85-88%) showing high sensitivity (95%, 95% CI 83-99%) and specificity (87%, 95% CI 85-87%), very high negative predictive value (99%, 95% CI 97-100%) and good positive predictive value (48%, 95% CI 41-50%) for central vertigo. Conclusion. Using the STANDING algorithm, non sub-specialists achieved good reliability and high accuracy in excluding stroke and other threatening causes of vertigo/unsteadiness.